Effect of the long-term intake of a casein hydrolysate on mucin secretion and gene expression in the rat intestine. (June 2017) - Fernández-Tomé, Samuel; Martínez-Maqueda, Daniel; Tabernero, María; Largo, Carlota; Recio, Isidra; Miralles, Beatriz
Highlights: Long-term casein hydrolysate intake increased rat intestinal mucin secretion. Relative expression of Muc2 and Muc4 genes was induced in ileum and colon tissues. In vivo potential of casein peptides on mucus gastrointestinal protection is proposed. Abstract: The aim of the present study was to investigate the in vivo effect on rat intestinal mucus production of a casein hydrolysate that had been previously shown a mucin stimulatory effect in human goblet cells (HT29-MTX). A significant rise of O-linked glycoproteins in faeces after 2 and 8 weeks of the casein hydrolysate intake was observed. In agreement with this increased secretion, the relative expression for the genes that encode the secreted MUC2 and the membrane-bound MUC3 was significantly increased in ileum and colon. Mucus material in the small intestine lumen of rats fed the casein hydrolysate was higher than that found in control rats, however the change did not reach statistical difference. This study confirms in vivo the potential effect on mucus gastrointestinal protection of this casein hydrolysate.